Sea Sand Abrasive Wear of Red Mud Micro Particle Reinforced Cissus quadrangularis Stem fiber/epoxy Composite - Iyyadurai Jenish; A. Felix Sahayaraj; M. Appadurai; E. Fantin Irudaya Raj; P. Suresh (Journal of Natural Fibers, 2022)
Natural fibers are growing attention in the replacement of synthetic glass fiber due to their unique properties. The present work focuses on the wear properties of Epoxy with Cissus quadrangularis Stem Fiber (CQSF) particulate-filled red mud composite using Taguchi L9 orthogonal array technique. A three-body wear test rig is done with four input parameters and three levels such as velocities (0.75 m/s, 1.5 m/s and 2.25 m/s), sliding distances (400 m, 600 m and 800 m), applied loads (10 N, 20 N and 30 N) and red mud filler (0%, 5% and 10%) to observe the wear behavior of the developed composites. The level of impact on specific wear rate due to various input parameters such as velocity, distance, load and filler was computed. The hardness of the samples was increased by 10.7% for 5 wt.% red mud addition and 14.2% for 10 wt.% of red mud addition. The overall mean for the signal-to-noise (S/N) ratio of the specific wear rate of the specimen was found to be 34.62 dB, respectively. Finally, the experimental result and predicted theoretical result were validated after taking the conformation experiment. The wear mechanism of the composite materials after the abrasive wear test was substantiated using scanning electron microscope (SEM) analysis.